Research advancements in the purification technology and application of hen egg white lysozyme - Liang-Liang Chen; Wen-Pu Shi; Juan-Juan Yang; Chen-Li Jiao; Pei-Feng Wei (Applied Food Research)
The lysozyme obtained from hen egg white (HEWL) is considered as one of the most prevalent natural proteins with extensive investigations conducted on it. It has also found wide-ranging applications in various fields such as food industry, scientific researches, medical treatments as well as material developments. This article provides a comprehensive review on different techniques used for isolating and purifying HEWL along with exploring its versatile uses in aforementioned areas to establish a fundamental reference for further development and utilization of this natural protein.